Stres Mempengaruhi Efikasi Diri Ibu Menyusui Neonatus Sakit yang Dirawat di Ruang Perawatan Neonatus - Sulupadang, Prishilla; Waluyanti, Fajar Tri; Allenidekania, Allenidekania (Health Information : Jurnal Penelitian, 2022)
Breastfeeding is still an obstacle for some mothers who have sick neonates who are receiving treatment at the hospital. Breastfeeding self-efficacy is related to the duration of breastfeeding which has an impact on the mother's success in breastfeeding at least exclusively. The purpose of this study was to identify factors related to breastfeeding self-efficacy in mothers of sick neonatal care room. This study used a cross-sectional design, 88 respondents were recruited using a consecutive sampling method, using a questionnaire that had been tested for validity first, namely the Breastfeeding self-efficacy scale short form (BSE-SF) and Edinburgh Postnatal Depression Scale (EPDS) questionnaires, husband's support, family support, and friend support. The results of the Chi square analysis showed that there was no relationship between breastfeeding self-efficacy in mothers with maternal age, mother's education, family income, experience of breastfeeding mothers, experiences of others breastfeeding their babies, health education support, husband support, family support, and friend support with p value > 0.05, but it was found that stress factors were associated with breastfeeding self-efficacy in mothers with sick neonates (p=<0.01). Stress is a factor associated with breastfeeding self-efficacy in mothers with sick neonates.